Study of impact of art performance level of blue laser technology applications and its control - Mohanad H. Ali; Mahmood H. Enad; Jasim Mohmed Jasim; Rawaa A. Abdul-Nab; Nadia Alani (Institute of Advanced Engineering and Science, 2020)
In this work; we present an enhancement in blue laser diodes with new factors and applications for modern technology such as underwater telecommunications, bio-sensor and bio-medical systems etc. Years of advance meanwhile have much enhanced laser performance, and extremely improved their diversity, making lasers significant parts in scientific research, telecommunications, engineering, bio-medical imaging, materials working, and a swarm of other applications. This article viewing how laser technology has progressed to chance application requirements. The enhanced blue laser building diagrams to get a peak efficiency% at room temperature with modification. Moreover, we have as well estimated electro-optical performance packing of blue laser diodes been significantly various associated to GaAs laser method and novel developments and performances are required to enhance the optical power from anther laser diodes. Researchers need enhanced approaches to accurately make new the blue laser applications to use control of modern experimental measurements and optical communication.